PENGARUH HARGA TERHADAP PENAWARAN DAN PERMINTAAN MASKER SAAT PANDEMI COVID-19 DI DENPASAR BALI - Saortua Marbun; Kristina Liuk Berek (Universitas Triatma Mulya, 2021)
Masks have become a basic need for everyone in pandemic. This causes people to compete to buy masks. This resulted in an extreme spike in mask prices. The demand for masks has soared, resulting in a shortage of these products. The purpose of this study was to determine the effect of price on supply and demand in the midst of the Covid-19 Pandemic in Denpasar City. This study used a sample of 200 respondents consisting of 100 traders and 100 buyers. Data were obtained by distributing questionnaires using a Likert scale. The method of analysis used is multiple linear regression. Based on the analysis, it is found that the price has an effect on supply with a positive regression coefficient. Price has an effect on demand with a negative coefficient.